Hubungan Kadar Trombosit, Hematokrit, dan Hemoglobin dengan Derajat Demam Berdarah Dengue pada Pasien Anak yang Rawat Inap di BRSU Tabanan - Desak Putu Citra Udiyani; Ni Putu Aniek Mahayani; Ni Made Dwinda Handayani (Aesculapius Medical Journal, 2022)
Dengue Hemorrhagic Fever (DHF) is the top ten causes of hospitalization in pediatrics. Indonesia is a country with the highest dengue cases in Southeast Asia and Bali is among the top five highest dengue cases in Indonesia. Tabanan Regency is the district with the highest Case Fatality Rate (CFR) in Bali, which is 0.6%. Early and accurate diagnosis can determine the patient's prognosis, but the WHO classification of DHF has not been able to provide a definite value for the degree of DHF based on the results of an examination of platelets, hematocrit, and hemoglobin. The existence of a definite value from the examination of platelets, hematocrit, and hemoglobin for each degree of DHF is expected to determine the prognosis of DHF. This type of research is an analytical research method with cross-sectional study design. The data collection method used secondary data from medical records. The research sample was all DHF pediatric patients aged 0-18 years at BRSU Tabanan who met the inclusion and exclusion criteria obtained using a consecutive sampling technique with a total sample of 84 children. Data analyses are univariate and bivariate. The results of this study showed that there was a significant relationship between platelet levels and the degree of DHF (p = 0.023 and r = 0.248), there was a significant relationship between hematocrit levels and the degree of DHF (p = 0.045 and r = 0.219), and there was no significant relationship between hemoglobin values. with the degree of DHF (p=0.073 and r=0.196).